Degradation study of Vitamin C concentration in pomegranate using spectrometric method / Nur Ain Abdul Ghafar …[et al.] - Abdul Ghafar, Nur Ain; Mohd Jan, Sarah Laila; Ismail, Mardhiah; Md Isa, Nurun Nadhirah; Mat Hussin, Zurhana; Nawi, Liliwirianis (2016)
Sunnah food products such as pomegranate, dates, honey and others are gain lots attention of Muslim customer nowadays. Pomegranate sold in commercial market in form of extract, juice or vinegar. Famous for its high antioxidant capacity and total phenolic contents, studies on pomegranate has gain researcher attention. The nutrition fact provided at the juice packaging does not necessarily show the exact amount of vitamin C as it claimed. The varieties of storage and packaging of juice make the consumer attracted to buy without think any consequences on the varieties. Either storage temperature or exposure of light have affected or not to the amount of vitamin C in the juice. This analysis was conducted to investigate the degradation of vitamin C concentration in pomegranate juice due to temperature and exposure of light using ultraviolet-visible (UV - Vis) spectrophotometers. Pomegranate juice samples from fresh fruits, tetra pak, glass bottle and aluminium container were stored in heat at 50 °C, cool temperature at 4°C and room temperature 20°C to 28 °C for 21 hours. For light exposure effect, the samples were stored at different condition which were under UV-light, sunlight and dark box. The vitamin C in fruits juice degraded in all temperature storage in contrast for the aluminium pack, which show increasing concentration of vitamin C. For the light exposure effect of the fruits juice sample, tetra pak, glass bottle and aluminium container samples showed concentration decrease in UV-light in 1 hour. The vitamin C in pomegranate juices were more easily degraded in the light exposure than in temperature storage.